Advances in Understanding Mitochondrial MicroRNAs (mitomiRs) on the Pathogenesis of Triple-Negative Breast Cancer (TNBC). (22nd March 2021) - Lin, Hung-Yu; Chu, Pei-Yi
Abstract : Triple-negative breast cancer (TNBC) is characterized by poor outcome and the most challenging breast cancer type to treat worldwide. TNBC manifests distinct profile of mitochondrial functions, which dictates reprogrammed metabolism, fosters tumor progression, and notably serves as therapeutic targets. Mitochondrial microRNAs (mitomiRs) are a group of microRNAs that critically modulate mitochondrial homeostasis. By a pathway-centric manner, mitomiRs tightly orchestrate metabolic reprogramming, redox status, cell apoptosis, mitochondrial dynamics, mitophagy, mitochondrial DNA (mtDNA) maintenance, and calcium balance, leading to an emerging field of study in various cancer types, including TNBC. We herein review the recent insights into the roles and mechanism of mitomiRs in TNBC and highlight its clinical value in diagnosis and prognosis as well as vital advances on therapeutics of preclinical and clinical studies.